The Use of European Union Funds by Enterprises in Peripheral Regions - Preliminary Research - Małgorzata JUCHNIEWICZ (Communications of International Proceedings, 2022)
The research was carried out by the method of a diagnostic survey with the use of a questionnaire in enterprises operating in peripheral regions of north-eastern Poland (in the following poviats: Bartoszyce, Braniewo, Ketrzyn and Lidzbark Warminski). The opinion of the owners (managers) of enterprises was established as regards the conditions for the use of European Union funds by enterprises in peripheral regions. The most important barrier related to the acquisition of EU funds by entrepreneurs from the studied counties was bureaucracy and the formalization of EU applications. If entrepreneurs received aid funds from the EU, they would first of all allocate them to the purchase of machinery, equipment and vehicles.
Keywords: European Union funds; peripheral regions; regional development.